2017
DOI: 10.3892/mco.2017.1372
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of late adverse events in proton beam therapy for prostate cancer

Abstract: The efficacy and safety of proton beam therapy (PBT) were retrospectively evaluated in 111 consecutive patients with prostate cancer who underwent definitive PBT between 2008 and 2012. Following exclusion of 18 patients due to treatment suspension, loss to follow-up, and histology, the analysis included 93 patients with a median age of 68 years (range, 49–81 years). A total of 7, 32 and 54 prostate cancer patients were classified as low-, intermediate- and high-risk, respectively, as follows: High-risk, T≥3a o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The early treatments of PCa include surgical treatment, androgen blockade and radiotherapy, but most patients still suffered from recurred tumors which will destroy the bone marrow and lead to death ( 11 ). Therefore, it is urgent to identify the molecular mechanisms to confirm potential effective therapeutic targets for improving patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…The early treatments of PCa include surgical treatment, androgen blockade and radiotherapy, but most patients still suffered from recurred tumors which will destroy the bone marrow and lead to death ( 11 ). Therefore, it is urgent to identify the molecular mechanisms to confirm potential effective therapeutic targets for improving patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Late grade 2 GI rectal bleeding was also observed in four patients. Analysis in this study showed that the use of anticoagulants is a positive prognostic factor for the development of GI toxicity [9].…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Fiorino et al, the risk of experiencing ≥grade 2 GI and GU is about 5%–20% [8]. With the materialization of image guided radiotherapy (IGRT), 3-dimensional conformal radiotherapy (3D-CRT) and intensity modulated radiotherapy (IMRT), the risk of toxicity on the organs at risk (OAR), namely the bladder, rectum, and seminal vesicle were decreased to 5%–10% [9]. The use of proton beams in radiation therapy further reduces this probability with its characteristic Bragg peak, where protons halt at a determined depth, analogous to its energy.…”
Section: Introductionmentioning
confidence: 99%
“…The energy of 6‐MV, 10‐MV, 15‐MV, and 18‐MV was employed for X‐ray beams, and that of 250 MeV and 400 MeV/nucleon for proton and carbon‐ion beams respectively. A prescribed dose of 78 Gy/39 fr, 78 Gy(RBE)/39 fr, and 66 Gy(RBE)/20 fr was assumed in the use of X‐ray, proton, and carbon‐ion beams, respectively, where the relative biological effectiveness (RBE) was assumed to be 1.1 and 2.36 for proton and carbon‐ion, respectively. In the simulation, a distance of 50 cm ( Y = 50 cm in superior‐inferior (SI) direction) was assumed from the center of the irradiation field to a CIED, where the IEC patient coordinate system was employed.…”
Section: Methodsmentioning
confidence: 99%